Scotland's Drug Criminality: Organized Crime Group (S) and Illegal Governance. Issue 4 (3rd April 2021) - Holligan, Chris; McLean, Robert; Rice, Gareth
ABSTRACT: Organized crime has been on the rise during the past decade. During that time, Scotland was home to more youth gangs than London, with Glasgow alone providing a base for around 170 youth gangs. However, more recent trends highlight a shift toward more organized criminal activity (OCA). The majority of Organized Criminal Gangs (OCGs) are involved in the illegal drugs trade, as well as fraudulent businesses and other such activities in an effort to legitimize or conceal illegal financial capital from rivals and police. This process has resulted in a steady decline of generalized violence. Although, there has been a simultaneous increase in high profile incidents, such as shootings and gangland assassinations. Drawing upon data gathered in the field, the authors support this view and argue that, while a number of factors effect divergent trends, illegal governance undoubtedly is present in criminogenic space which in turn impacts upon gang organization and behavior. OCGs look to impose control over physical territory via occasional incidents in order to outwardly project psychological fear which ensures maximum control over the populations.